UDK 620.20 ANALYSIS OF SOLAR ENERGY DEVICES - Boynazarov, Bekzod; Nasretdinova, Feruza; Uzbekov, Mirsoli (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Analytical research on the effective use of solar energy in the conditions of Uzbekistan was conducted in the article. It was mainly analyzed that solar energy devices are more effective in using them according to their goals. The article contains theoretical conclusions based on the results of the research methods used in the literature. The data was analyzed using the "Methodological analysis" and "Meta-analysis" methods.